Effects of tapping system and rubber tree age on quantity and quality of latex - Chumsri, Tatsanee; Kongsawadworakul, Panida; Vinijsanun, Tavorn; Chintakovid, Watcharra (Asia-Pacific Journal of Science and Technology, 2017)
In this study, the quantity and quality of latex of rubber tree (Hevea brasiliensis Muell. Arg.)as affected by 2 types of tapping system, one-half of trunk circumference (S/2) and one-third of trunk circumference (S/3), were studied using rubber trees grown at Nakorn Si Thammarat province. Clone RRIM600 at 2 ages of tree: less than 10 years and more than 10 years after tree opening were compared.Two clones, RRIM600 and PB255, of trees tapped for longer than 5 years were also compared.The latex was collected at 2nd and 4th h after tapping (n=10).Yield, % dry rubber content (DRC) and % lutoids were recorded.S/2 tapping system provided significantly higher yield than S/3 but did not affect % DRC and % contaminants. Rubber tree tapped for longer than 10 years gave more yield and % DRCthan those tapped for less than 10 years. RRIM600 gave higher yield and %DRC than PB255. Moreover, contaminants (e.g., lutoids) were found largely at 4th h after tapping, especially in S/2 of PB255 trees tapped more than 10 years.